Agentive and Independent Older Female Adult in Strong Woman Gang Nam-Soon: Going Against Prevalent Gendered Ageism in K-Dramas - Yuliyanto Chandra (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This article explores the representation of an older female adult (OFA) in the Korean drama Strong Woman Gang Nam-Soon. While scholarship on OFA has revealed their lack of positive representation—resulting in multifarious detriments—literature on OFA in K-drama is considerably scanty. Hence, this article employs content analysis, focusing on one of the protagonists, Gil Jung-Gan. Additionally, to enrich the discussion, industrial analysis was also carried out. The critical discussion focuses on three major aspects: 1) the feminist perspective influencing the K-drama industry, 2) principles of agentive and powerful OFA character, and 3) beauty and successful aging discourse. This article argues that the positive representation of Gil Jung-Gan is the manifestation of the progressive movement and influence of local and global feminism, which can be traced through the fulfillment of the majority of the principles. Additionally, the series incorporates successful aging discourse to represent Gil Jung-Gan as an agentive and non-traditional OFA, which is achieved mainly by physical appearance and social engagement.